Gender Expression, Sexual Orientation and Pain Sensitivity in Women - Jacob M Vigil; Lauren N Rowell; Charlotte Lutz (Pain Research and Management)
BACKGROUND: Despite a growing body of literature investigating sex differences with regard to pain, surprisingly little research has been conducted on the influence of various aspects of self-identity, including gender expression and sexual orientation, on pain sensitivity within each sex, particularly among women. In men, dispositional femininity is linked to greater clinical pain and trait masculinity is associated with higher pain thresholds.